PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI MEDIASI ( Studi pada Badan Kepegawaian Daerah Kabupaten Rembang ) (Students' Journal of Economic and Management, 2013)
The purpose of this study is to analyze the effects of compensation and carrier development on the job performance  with motivation as  mediator  in Rembang Regional Civil Service Board. The population in this study is the civil service of Rembang Regional Civil Service Board that amounts to 58 people.  This study  use cencuss methode for collecting data , which is  the whole population is taken into account. The results of this study correctly proved that model’s ability to explain correctly , compensation variable’s influence , carrier development and motivation to job performance  is amounted 43,9 % . Whereas the other’s is amounted 56,1 % as explained by variables outside the data-model. Mediating effect test proved that the effects of compensation and carrier development on the job performance are not mediated by motivation .   Kata Kunci: kompensasi, pengembangan karier, motivasi dan kinerja pegawai.